Simulasi Pengaruh Jarak Saddle Berbahan SA 516 Gr.70 pada Bejana Tekan Horizontal Menggunakan Software Autodesk Inventor 2019 - Krisdiyanto, Krisdiyanto (Universitas Muhammadiyah Yogyakarta, 2018)
Pressure vessel is a complex structure. Pressure vessel is designed to resist internal pressure loads, temperature loads, external loads, etc. Horizontal pressure vessel is a type of pressure vessel. Horizontal pressure vessel is supported by two saddles. Saddle is used to hold loads from pressure vessel. Length variations saddle and tangent pressure vessel is affected to stress and displacement. Maximum stress values of pressure vessel should be considered so the failure of structure can be decreased. This research aims to review the effect length variations saddle and tangent pressure vessel to maximum stress and displacement.